Public economics : theory and policy : essays in honor of Dr. Amaresh Bagchi - Govinda Rao, M.; Rakshit, Mihir; Bagchi, A. (Amaresh) (New Delhi : SAGE, 2011)
Amaresh Bagchi, Indian economist; contributed articles.
Includes bibliographical references and index.
Keywords: Fiscal policy; Finance, Public